Methodology of institutional changes in university education - Volnistaya, Marina G. (Journal of the Belarusian State University. Sociology, 2021)
The article analyses the problem of institutional changes at the university as an academic system in a pandemic. The academic values of the modern university professional community include the social responsibility of the university. In the new conditions, this value dimension of the role of the university in the life of society determines the main directions of research on transformations of the university as the most important social institution. The factors of institutional sustainability of university education are determined. The author examines the role of the university in overcoming global and local risks.